Pengaruh Gaya Kepemimpinan Transformasional dan Lingkungan Kerja terhadap Kinerja Karyawan di UD. Dua Bersaudara - Vina Linda Maulah; Imam Baidlowi; Toto Heru Dwihandoko (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to analyze the influence of transformational leadership style and work environment on employee performance at UD. Dua Bersaudara. The background of this study is based on the importance of leadership that is able to provide inspiration, motivation, and support in increasing employee productivity. On the other hand, a conducive work environment is also a key factor that can create comfort, increase morale, and foster employee loyalty to the company. The method used in this study is a quantitative method with an associative approach, where data were obtained through questionnaires distributed to 50 respondents who are all employees of the company. The collected data were then analyzed using multiple linear regression with the help of the SPSS program version 25. The results of the analysis show that transformational leadership style has a significant influence on employee performance. In addition, the work environment also plays an important role in improving employee outcomes. Simultaneously, both variables are proven to have a significant influence on employee performance. These findings indicate that the application of an appropriate transformational leadership style, such as providing a clear vision, being a role model, and encouraging innovation, can improve work quality and employee productivity. Likewise, creating a supportive work environment, such as good communication, adequate work facilities, and a harmonious work atmosphere, will encourage employees to work more effectively. Therefore, it can be concluded that creating a supportive work environment combined with effective leadership can significantly enhance employee performance. This research also provides practical implications for home industries, encouraging them to pay more attention to leadership aspects and work environment conditions in an effort to increase competitiveness.